Efficacy and Safety of Ocrelizumab in Active Proliferative Lupus Nephritis: Results From a Randomized, Double‐Blind, Phase III Study1. Issue 9 (26th August 2013) - Mysler, Eduardo F.; Spindler, Alberto J.; Guzman, Renato; Bijl, Marc; Jayne, David; Furie, Richard A.; Houssiau, Frédéric A.; Drappa, Jorn; Close, David; Maciuca, Romeo; Rao, Kajal; Shahdad, Saba; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate the efficacy and safety of ocrelizumab in patients with class III/IV lupus nephritis (LN). Methods Patients were randomized 1:1:1 to receive placebo, 400 mg ocrelizumab, or 1, 000 mg ocrelizumab given as an intravenous infusion on days 1 and 15, followed by a single infusion at week 16 and every 16 weeks thereafter, accompanied by background glucocorticoids plus either mycophenolate mofetil (MMF) or the Euro‐Lupus Nephritis Trial (ELNT) regimen (cyclophosphamide followed by azathioprine). The study was terminated early due to an imbalance in serious infections in ocrelizumab‐treated patients versus placebo‐treated patients. We report week 48 efficacy data for patients receiving ≥32 weeks of treatment (n = 223) and safety results for all treated patients (n = 378). Results The overall renal response rate was 54.7%, 66.7%, 67.1%, and 66.9% in the placebo‐treated, 400 mg ocrelizumab–treated, 1, 000 mg ocrelizumab–treated, and combined ocrelizumab‐treated groups, respectively. The associated treatment difference versus placebo for the combined ocrelizumab‐treated groups was 12.7% (95% confidence interval [95% CI] −0.8, 26.1) (P = 0.065), with similar differences observed for both ocrelizumab‐treated groups. Ocrelizumab versus placebo treatment differences were apparent in patients receiving the background ELNT regimen, but not in those receiving background MMF. A numerically greater proportion of ocrelizumab‐treated patients had a ≥50% reduction in the urinary protein:urinary creatinine ratio at 48 weeks compared with placebo‐treated patients (placebo‐treated patients, 58.7%; 400 mg ocrelizumab–treated patients, 70.7%; 1, 000 mg ocrelizumab–treated patients, 68.5%). Serious adverse events occurred in 27.2% of placebo‐treated patients, 35.7% of 400 mg ocrelizumab–treated patients, and 22.0% of 1, 000 mg ocrelizumab–treated patients. Corresponding serious infection rates (events/100 patient‐years) were 18.7 (95% CI 12.2, 28.7), 28.8 (95% CI 20.6, 40.3), and 25.1 (95% CI 17.4, 36.1), respectively. The imbalance in serious infections with ocrelizumab occurred with background MMF but not with the background ELNT regimen. Conclusion In patients with active LN, overall renal response rates with ocrelizumab were numerically but not statistically significantly superior to those with placebo. Ocrelizumab treatment was associated with a higher rate of serious infections in the subgroup receiving background MMF.